Decrease in fasting insulin secretory function correlates with significant liver fibrosis in Japanese non‐alcoholic fatty liver disease patients. Issue 5 (9th June 2020) - Araki, Norimasa; Takahashi, Hirokazu; Takamori, Ayako; Kitajima, Yoichiro; Hyogo, Hideyuki; Sumida, Yoshio; Tanaka, Saiyu; Anzai, Keizo; Aishima, Shinichi; Chayama, Kazuaki; Fujimoto, Kazuma; Eguchi, Yuichiro
Abstract: Background and Aim: Non‐alcoholic fatty liver disease (NAFLD) is typically associated with metabolic syndrome and diabetes, and insulin resistance is involved in its pathogenesis. However, the relationship between insulin secretion and NAFLD is unclear. We aimed to characterize the relationship between fasting insulin secretory function (ISF), evaluated using the homeostatic model assessment‐beta cell function (HOMA‐β) and the severity of fibrosis during NAFLD. Methods: A‐β was calculated in 188 patients with biopsy‐confirmed NAFLD, and the correlations between Log HOMA‐β and clinical parameters, including hepatic fibrosis, were calculated. Results: Log HOMA‐β was significantly lower in NAFLD patients with significant fibrosis (stages 2–4) than in those in the early stages (stages 0–1) (median [interquartile range]) (2.1 [1.9–2.4] vs 2.0 [1.8–2.2], P = 0.04). The prevalence of significant fibrosis decreased with increasing Log HOMA‐β: it was 59.2% in participants with low ISF (Log HOMA‐β < 1.85), 43.6% in those with intermediate ISF (1.85 ≤ Log HOMA‐β < 2.25), and 68.0% in those with high ISF (Log HOMA‐β ≥ 2.25). Patients with lower Log HOMA‐β had lower current body mass index (BMI), BMI at 20 years of age, and peak lifetime BMI than patients with intermediate or high Log HOMA‐β. Conclusions: Fasting ISF decreased alongside the development of liver fibrosis in NAFLD, suggesting that an impaired β cell function has a characteristic finding of significant liver fibrosis in relatively nonobese Japanese patients. Abstract : Japanese patients with NAFLD have significant fibrosis with reduced insulin secretion. These patients also tended to be significantly non‐obese.